Phthalide synthesis through dehydrogenated lactonization of the C(sp3)–H bond by photoredox catalysis. Issue 20 (1st October 2021) - Liu, Hui; Liu, Chao; Chen, Shanyi; Lai, Qihong; Lin, Yulin; Cai, Zhixiong; Huang, Mingqiang; Cai, Shunyou
Abstract : An efficient method for the direct oxidative lactonization of the C(sp 3 )–H bonds of benzyl via visible-light-induced photoredox catalysis. The metal-free protocol delivers diverse phthalides using O2 as the sole terminal oxidant at room temperature. Abstract : A practical and efficient method is established for the direct oxidative lactonization of the C(sp 3 )–H bonds relying on visible-light-induced photoredox catalysis. This protocol expediently allows the delivery of diverse phthalides using oxygen as the sole terminal oxidant under metal-free conditions at room temperature. Notably, the choice of an appropriate hydrogen atom transfer (HAT) cocatalyst is revealed to be critical for the success of this process.